War Crimes - Gilbertson, Tristan (Victoria University of Wellington Law Review, 1995)
This article examines the status of crimes against humanity in New Zealand and international law at the time of the Second World War. It argues, on the basis of an historical examination of the laws and customs of war, that crimes against humanity were established in customary international law over 100 years before the War. This conclusion effectively eliminates any question of retroactive punishment of these crimes at Nuremberg and, by extension, more recent war crimes trials. The article then examines the status of crimes against humanity in New Zealand municipal law. It considers whether crimes against humanity form part of New Zealand law under the common law doctrine of incorporation or whether it would be necessary to legislate for trials for these crimes to take place here. The article concludes by suggesting the form any New Zealand legislation should take on the basis of a comparative analysis of war crimes legislation in other jurisdictions.